2019
DOI: 10.1007/s40843-019-1185-2
|View full text |Cite
|
Sign up to set email alerts
|

Calix[6]quinone as high-performance cathode for lithium-ion battery

Abstract: Organic quinone compounds have attracted wide attention due to their high theoretical capacities. Here, a novel cyclic macromolecular calix[6]quinone (C6Q), which possesses 6 p-quinone units and can provide 12 electrochemical active sites, has been applied as a promising cathode material in lithium ion batteries (LIBs). The as-fabricated LIBs exhibited an initial specific capacity as high as 423 mA h g −1 (C theo = 447 mA h g −1) at 0.1 C. After 100 cycles, the capacity of C6Q maintained at 216 mA h g −1 , and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 43 publications
0
33
0
1
Order By: Relevance
“…Another way to solve the solubility problem of quinones is to composite them with other material. [23][24][25][26][27][28][29] For example, an Al 2 O 3 layer (2 nm) was successfully deposited on Na 2 DBQ electrode surface to suppress the dissolution of Na 2 DBQ, which showed significant enhancement on the SIB performance (reversible capacity of 212 mAh g −1 over 300 cycles). [23] Wu et al [24] immobilized CNTs onto Na 2 DBQ by a spray drying method, and the as obtained nanocomposite delivered a high reversible capacity (259 mAh g −1 ) and excellent rate performance (142 mAh g −1 at 7 C).…”
Section: Co Bonded Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another way to solve the solubility problem of quinones is to composite them with other material. [23][24][25][26][27][28][29] For example, an Al 2 O 3 layer (2 nm) was successfully deposited on Na 2 DBQ electrode surface to suppress the dissolution of Na 2 DBQ, which showed significant enhancement on the SIB performance (reversible capacity of 212 mAh g −1 over 300 cycles). [23] Wu et al [24] immobilized CNTs onto Na 2 DBQ by a spray drying method, and the as obtained nanocomposite delivered a high reversible capacity (259 mAh g −1 ) and excellent rate performance (142 mAh g −1 at 7 C).…”
Section: Co Bonded Compoundsmentioning
confidence: 99%
“…Chen et al [25] found that 2, 3-dicyano-5, 6-dichloro-1, 4-benzoquinone (DDQ) with 60% carbon black exhibited high reversible capacity of 456 mAh g −1 at 0.1 A g −1 and cycling life with 436.5 mAh g −1 over 100 cycles for SIBs. Recently, Huang et al [26][27][28][29] investigated the effect of carbon materials on the organic electrode materials performance. The dissolution of C4Q can be effectively restricted by encapsulating it in CMK-3, and the stability and electronic conductivity of C4Q/CMK-3/SWCNTs are intensified by the 3D conductive network.…”
Section: Co Bonded Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the strategy of introducing substituents, designing multi‐ p ‐benzoquinone molecules (i.e., BQ oligomers) with relatively large size could also decrease the solubility. [ 22–25 ] Recently, Kwon and coworkers studied a stereoscopic triptycene triquinone molecule (Figure S1b, Supporting Information), [ 22 ] which delivered a high initial capacity of 387 mAh g −1 (83% utilization of carbonyl groups) but a low capacity remained after 100 cycles (<50 mAh g −1 ). Chen's group reported another two kinds of multi‐ p ‐benzoquinone molecules with three‐dimensional macrocyclic structures, the calix[4]quinone [ 23 ] (Figure S1c, Supporting Information) and pillar[5]quinone [ 24 ] (Figure S1d, Supporting Information), bearing four and five BQ units, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, both of them displayed rapid capacity fading in organic liquid electrolytes due to their serious dissolutions. Recently, Zhang's group reported a similar but larger macrocyclic molecule bearing six BQ units, calix[6]quinone (Figure S1e, Supporting Information), [ 25 ] and the cycling performance is enhanced but still suffered from rapid capacity decay with a low capacity retention of ≈220 mAh g −1 after 100 cycles.…”
Section: Introductionmentioning
confidence: 99%